Optimalisasi Kerja Alat Dengan Sistem Antrian Satu Setengah Untuk Meningkatkan Efisiensi Kerja, Dan Mengoptimalkan Produksi Pada Pengupasan Overburden Di Pit Central Jobsite Adaro Indonesia PT. Saptaindra Sejati - Andhika Hidayat; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. In the year of 2018, PT. Saptaindra Sejati has not been able to reach the overburden production target set by PT. Adaro Indonesia for the Pit Central is 45,000.00 m³, while the actual production achieved is 43,477,658 m³. In mining activities at PT. Saptaindra Sejati often occurs in the queue of transportation equipment and sometimes the digging tool is waiting. This is caused by an irregular device circulation system. In order to deal with the possibility of a queue of transportation equipment, the method of queuing for transportation is better than now, namely by the one and a half queue method. The one queue method is as applied as possible so that the hanging tool loading time when the spotting time is zero, so that work efficiency and productivity can be increased and production costs can be streamlined. The working efficiency of the loading digger after the application of the one and a half queuing method has increased by 4.6%, while the working efficiency of the conveyance has increased by 0.5%. Productivity of the digging tool at the Pit Central after the application of the one and a half queue method has increased from 2,950.38 m3/ hour to 3,282.24 m3/ hour, while the transportation equipment productivity has increased from 2,622.21 m3/ hour to 2,990.72 m3/ hour . To achieve harmony in the workings of the tool after optimization, it is necessary to increase the number of transport equipment. The production costs at the Pit Central for stripping overburden from the 4000 class loading tool have a profit of 0.396 / m3 after the application of the one and a half queue method.